2021
DOI: 10.3390/genes12081190
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogenetic Analysis of the AIG Family in Vertebrates

Abstract: Androgen-inducible genes (AIGs), which can be regulated by androgen level, constitute a group of genes characterized by the presence of the AIG/FAR-17a domain in its protein sequence. Previous studies on AIGs demonstrated that one member of the gene family, AIG1, is involved in many biological processes in cancer cell lines and that ADTRP is associated with cardiovascular diseases. It has been shown that the numbers of AIG paralogs in humans, mice, and zebrafish are 2, 2, and 3, respectively, indicating possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…The difference was contributed by tandem gene duplicates in C. hemipterus , including a cluster of 9 FAR-17a/AIG1-like protein coding genes on chromosome 16 (Supplementary Figure 6A). Although all annotated FAR-17a/AIG1-like proteins were expressed in C. hemipterus (Supplementary Figure 6B), little is known about their function in insects as FAR-17a/AIG1-like proteins were mainly characterized in vertebrate models as an androgen-responsive gene and a role player in cancer-related processes (Huang et al 2021). On the other hand, in addition to known insect tetraspanin orthologous families (Huang et al 2005), the expansion in tetraspanin was contributed by a newly identified family termed “N-3”, which was also found in hemipteran Orius laevigatus (Supplementary Figure 7 and 8).…”
Section: Resultsmentioning
confidence: 99%
“…The difference was contributed by tandem gene duplicates in C. hemipterus , including a cluster of 9 FAR-17a/AIG1-like protein coding genes on chromosome 16 (Supplementary Figure 6A). Although all annotated FAR-17a/AIG1-like proteins were expressed in C. hemipterus (Supplementary Figure 6B), little is known about their function in insects as FAR-17a/AIG1-like proteins were mainly characterized in vertebrate models as an androgen-responsive gene and a role player in cancer-related processes (Huang et al 2021). On the other hand, in addition to known insect tetraspanin orthologous families (Huang et al 2005), the expansion in tetraspanin was contributed by a newly identified family termed “N-3”, which was also found in hemipteran Orius laevigatus (Supplementary Figure 7 and 8).…”
Section: Resultsmentioning
confidence: 99%
“…6 A ). To verify the syntenic relationships I only suggest to run a Multiple Sequence Alignments (MSA) scanning algorithm if necessary [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%